You and you pronouns of address in Lima: sociolinguistic variation - Llanto Chávez, Lilia (2007)
This study focuses on the empirical observation of the use of the second person personal pronouns tú and usted, and the attitude towards the treatment with such pronouns by Spanish speakers residing in the city of Lima (Peru). The result of the research shows differences where the pronoun tú acquires the sense of confidence and/or affectivity as opposed to usted whose expression implies distance and verticality from top to bottom, but there are also uses that indicate a certain degree of linguistic insecurity.